Neurosyphilis: Diagnostic Challenges and Public Health Relevance – A Case Report (Kerala Journal of Psychiatry, 2025)
Background: Syphilis, caused by Treponema pallidum, remains a diagnostic challenge due to its varied clinical manifestations. Neurosyphilis, a late-stage complication, can mimic psychiatric disorders and lead to misdiagnosis.Case Report: A middle-aged woman presented with progressive cognitive decline, personality changes, and psychotic symptoms. She was initially mistaken for a primary psychiatric illness. Serological testing confirmed neurosyphilis, and treatment with intravenous penicillin resulted in marked improvement in neuropsychiatric features. This case emphasizes the importance of considering syphilis in atypical psychiatric presentations, particularly given its global resurgence.Conclusion: Early recognition and timely therapy are essential to prevent irreversible neurological damage, underscoring the need for heightened clinical vigilance and routine screening in at-risk populations.
Keywords: Neurosyphilis; Chronic meningovascular syphilis; Organic psychosis; Neuropsychiatry; Public health